Don't use a calculator.

Algebra Level 2

Simplify 23 + 408 23 408 \sqrt{23+\sqrt{408}} -\sqrt{23-\sqrt{408}} .

2 7 2\sqrt{7} 2 6 2\sqrt{6} 2 5 2\sqrt{5} 4

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

In general, let S = a + b a b S = \sqrt{a + \sqrt{b}} - \sqrt{a - \sqrt{b}} for positive reals a , b . a,b.

Now S 2 = ( a + b ) + ( a b ) 2 ( a + b ) ( a b ) = 2 ( a a 2 b ) . S^{2} = (a + \sqrt{b}) + (a - \sqrt{b}) - 2\sqrt{(a + \sqrt{b})(a - \sqrt{b})} = 2(a - \sqrt{a^{2} - b}).

Assuming that a b a \ge \sqrt{b} it is clear that S 0 , S \ge 0, and so S = 2 ( a a 2 b ) . S = \sqrt{2(a - \sqrt{a^{2} - b})}.

In this case a = 23 , b = 408 , a = 23, b = 408, and thus

S = 2 ( 23 529 408 ) = 2 ( 23 11 ) = 24 = 2 6 . S = \sqrt{2(23 - \sqrt{529 - 408})} = \sqrt{2(23 - 11)} = \sqrt{24} = \boxed{2\sqrt{6}}.

Aquilino Madeira
Jul 26, 2015

23 + 408 23 408 = = ( 1 ) 17 + 6 ( 17 6 ) = 17 + 6 17 + 6 = 2 6 ( 1 ) A ± B = A + C 2 ± A C 2 , C 2 = A 2 B 2 \begin{array}{l} \sqrt {23 + \sqrt {408} } - \sqrt {23 - \sqrt {408} } = \\ \mathop = \limits_{(1)} \sqrt {17} + \sqrt 6 - \left( {\sqrt {17} - \sqrt 6 } \right)\\ = \sqrt {17} + \sqrt 6 - \sqrt {17} + \sqrt 6 \\ = 2\sqrt 6 \\ \\ (1)\sqrt {A \pm \sqrt B } = \sqrt {\frac{{A + C}}{2}} \pm \sqrt {\frac{{A - C}}{2}} \quad ,\quad {C^2} = {A^2} - {B^2} \end{array}

Let { ( a + b ) 2 = 23 + 408 ( a b ) 2 = 23 408 where a > b \space \begin{cases} (\sqrt{a}+\sqrt{b})^2 = 23 + \sqrt{408} \\ (\sqrt{a}-\sqrt{b})^2 = 23 - \sqrt{408} \end{cases} \quad \text{where } a > b

23 + 408 23 + 408 = ( a + b ) ( a b ) = 2 b \Rightarrow \sqrt{23+\sqrt{408}} - \sqrt{23+\sqrt{408}} = (\sqrt{a}+\sqrt{b}) - (\sqrt{a} - \sqrt{b}) = 2\sqrt{b}

( a + b ) 2 = a + b + 2 a b = 23 + 408 \begin{aligned} (\sqrt{a}+\sqrt{b})^2 & = a+b+2\sqrt{ab} = 23 + \sqrt{408} \end{aligned}

{ a + b = 23 a = 23 b 2 a b = 408 a b = 102 ( 23 b ) b = 102 b 2 23 b + 102 = 0 ( b 6 ) ( b 17 ) = 0 \Rightarrow \begin{cases} a + b = 23 & \Rightarrow a = 23 - b \\ 2\sqrt{ab} = \sqrt{408} & \Rightarrow ab = 102 \quad \Rightarrow (23-b)b = 102 \\ & \Rightarrow b^2 - 23b + 102 = 0 \quad \Rightarrow (b-6)(b-17) = 0 \end{cases}

Since a > b a = 17 b = 6 \space a > b \quad \Rightarrow a = 17 \quad \Rightarrow b = 6

23 + 408 23 + 408 = 2 b = 2 6 \Rightarrow \sqrt{23+\sqrt{408}} - \sqrt{23+\sqrt{408}} = 2\sqrt{b} = \boxed{2\sqrt{6}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...